Dukungan Sosial dan Motivasi Mencari Kerja terhadap Kesiapan Kerja pada Pemuda Desa Keper yang Baru Lulus Sekolah Menengah Atas - Hadi, Mohammad Rofiq Al; Mariyati, Lely Ika (IDEA: Jurnal Psikologi, 2024)
The purpose of this study was to determine the relationship between social support and motivation to seek work on job readiness in youth of Keper village Sidoarjo. This is based on the phenomenon of the lack of job specialization after high school. This study used a quantitative correlation method. This study consists of three variables, namely the dependent variable (dependent variable), namely: work readiness variable (Y). While the independent variable (free variable), namely; variable social support and motivation to find work as the X variable. Respondents in this study amounted to 60 subjects from a population of 60 people using the Saturated Sample Technique in sample selection. Data analysis uses inferential statistical techniques, namely multiple regression analysis. The results show that there is a significant relationship between social support to job-seeking motivation and job readiness in youth of Keper Village, Sidoarjo.